Growth regulators in the vegetative development of Agave durangensis Gentry vitroplants - Dévora-Rodríguez, Daniela Guadalupe; Pulido-Díaz, Cecilia; Chávez-Simental, Jorge Armando; Ortiz-Sánchez, Ixchel Abby; Loera-Gallegos, Héctor Manuel; Prieto-Ruiz, José Ángel (Ecosistemas y Recursos Agropecuarios, 2021)
The effect of cytokinins and auxins on the production of adventitious shoots of Agave durangensis in vitro was studied. Germination was done in Murashige and Skoog (MS) culture medium at 50% concentration without growth regulators was used. The production and development of adventitious shoots was carried out in a 100% MS culture medium with cytokinins (KIN and BAP) and ANA as auxin, evaluating different concentrations in 12 treatments. The concentration of 4.0 mg L-1 of BAP without auxins presented better results in explant height, number of leaves per explant, number of shoots per explant and number of leaves per shoot. The presence of auxins only favored the height of the sprout in the treatment of 4.0 mg L-1 KIN and 0.4 mg L-1 ANA. Therefore, it is feasible to use only cytokinins on culture medium in the shoots production stage of A. durangensis.